Hypertext production on moddle to the teaching of the electromagnetism of the motor electric - Silva, Ricardo Barreto da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2013)
This paper describes the production by MOODLE of hypertexts for the study of electromagnetic phenomena necessary for understanding the operation of the electric motor. Were produced three hypertext with words and expressions connected to web pages which can be quickly and randomly accessed. The preliminary results demonstrate the potential of the web as a source of learning objects and MOODLE as a tool for management and production of hypertexts for teaching physics.